Tingkat stress calon guru pendidikan jasmani selama pandemi covid-19 - Wahyu Indra Bayu; Meirizal Usra; Giartama Giartama; Soleh Solahuddin; Herri Yusfi (Journal Of Sport Education (JOPE), 2022)
Since the spread of Covid-19 on a global scale, most efforts at the national level have been directed at mitigating the spread of the virus and physical harm, but little attention has been paid to the psychological impact of Covid-19 on mental health, especially in the early stages of the pandemic. This study aims to determine the stress level of prospective physical education teachers during the Covid-19 pandemic. The cross-sectional study was conducted using a self-administered online questionnaire. The measure of psychological distress was obtained using The Kessler Psychological Distresss Scale (K10). A total of 261 complete questionnaire results were included in the analysis. Male participants slightly dominated the sample (n = 171; 67.05%) than women (n = 86; 32.95%). Respondents were aged 18–21 years (mean 19.6 years, SD: 3.16). The results showed that the average candidate for physical education teachers at Sriwijaya University was at the "Okay" level with an average score of 20.02. Meanwhile, when analyzed based on the gender of the respondent, it was found that there was a difference in stress levels between men and women (F: 15,629; Sig. 0.000 < 0.05), while the year factor and the interaction between the year factor and gender had no difference. respondent's stress level (F: 0.84; Sig. 0.433 > 0.05; F: 1.801; Sig. 0.167 > 0.05). This shows that the academic level of students has no difference in the stress level of the respondents, while the gender factor has different stress levels. And there is no interaction between the year of class and gender in determining stress levels.Copyright © The Author (s) 2022Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.